Modern performing arts of Ukraine as lecture and practical lessons in the course with future teachers of musical art - Hevko, Ihor; Spolska, Olena; Xiaonan, Xie; Hongwei, Wu (Journal of Education, Health and Sport, 2022)
The purpose of the work is to highlight experimental methodical approaches to the representation of certain aspects of modern Ukrainian vocal art on the example of the organization of research, educational and performing activities of master’s students of the Faculty of Arts of V. Hnatyuk TNPU. The research methodology consists in the use of methods of historical and cultural discourse, historical and musicological positions on the problems of vocal art, in the implementation of activity and integrative approaches based on the example of art pedagogy. Attention is focused on the problem of representation of the main problems of the development of modern Ukrainian vocal art on the example of the organization of research, educational and performing activities of future music teachers. Taking into account the tasks of their professional training, the specifics and prospects of their future pedagogical and performing activities, we have already made attempts to extrapolate the history of performing schools to the content of the "Methodology of Music Education" course and the subjects of the school cycle, in particular, the reading of the "Artistic Culture of Ukraine" course during 2019–2020. The scientific novelty consists in the presentation of an integrative approach to the organization of the research, educational and performance activities of master’s students on the example of the interaction of teachers of specialized lecture-theoretical ("History of Ukrainian Music", "Contemporary Music"), research courses ("Fundamentals of Music and Pedagogical Research", "Methodology of Scientific research", "Fundamentals of musical interpretation") and practical disciplines ("Vocal") during 2020–2021. A number of examples of research work of master’s students are presented (essays, "musical quizzes", questionnaires, etc., related to the problems of modern musical art). A block of master’s research materials related to musical Ternopil, with the organization of the competition and festival movement, is separately allocated. Excerpts from essays of master’s students on the topic "Show business: pros and cons" are given. As examples of the cooperation of academic supervisors with vocal teachers, the content of master’s studies was clarified, respectively - programs of master’s students’ concerts. For example, creative projects "Song about a song", "Moment". Conclusions. We believe that the best examples of modern pop songs are an important contribution to the vocal art of Ukraine. Their role especially increases in periods of social challenges, war tragedies as a reaction-protest of artists and society in general. At the same time, it is an interesting research material, a high-value performing and educational repertoire, which should be qualitatively presented in performance classes of art institutions. So, the layer of popular musical culture and performance, represented by the activities of famous soloists and bands from different regions of Ukraine, participants of the competition-festival movement in Ukraine and abroad, was and remains the subject of thorough comparative research.